Adhesion of anaerobic bacteria to platelet containers. Issue 2 (6th March 2014) - Kumaran, D.; Kalab, M.; Rood, I. G. H.; de Korte, D.; Ramirez‐Arcos, S.
<x xml:space="preserve">Abstract</x> Anaerobic Propionibacterium acnes and Staphylococcus saccharolyticus are frequently isolated during platelet screening with anaerobic culture methods. Although neither P. acnes nor S. saccharolyticus proliferates during platelet storage, both species survive well in this environment. This study was aimed at determining whether strains of P. acnes and/or S. saccharolyticus form surface‐attached bacterial cell aggregates, known as biofilms, under platelet storage conditions. We report that these organisms are able to adhere to the inner surface of platelet containers in tight interaction with activated platelets.